Fundamentals and current strategies for Peripheral Nerve Repair and Regeneration - Carvalho, Cristiana Rodrigues (2020)
A body of evidence indicates that peripheral nerves have an extraordinary yet limited capacity to regenerate after an injury. Peripheral nerve injuries have confounded professionals in this field, from neuroscientists to neurologists, plastic surgeons, and the scientific community. Despite all the efforts, full functional recovery is still seldom. The inadequate results attained with the â gold standardâ autograft procedure still encourage a dynamic and energetic research around the world for establishing good performing tissue engineered alternative grafts. Resourcing to nerve guidance conduits, a variety of methods have been experimentally used to bridge peripheral nerve gaps of limited size, up to 30-40 mm in length, in humans. Herein, we aim to summarize the fundamentals related to peripheral nerve anatomy and overview the challenges and scientific evidences related to peripheral nerve injury and repair mechanisms. The most relevant reports dealing with the use of both synthetic and natural-based biomaterials used in tissue engineering strategies when treatment of nerve injuries is envisioned are also discussed in depth, along with the state-of-the-art approaches in this field.